Academics' manufacturing of counter-narratives as knowledge resistance of official hegemonic narratives in identity conflicts. Issue 2 (3rd May 2020) - Herath, Dhammika; Schulz, Michael; Sentama, Ezechiel
ABSTRACT: This article illustrates how official hegemonic narratives of armed conflicts and history are resisted by academics by generating counter-narratives and how this affects the public perception of identity conflicts. Due to the relatively high status of academics, critical and alternative knowledge production serve as a tool for resistance against the mainstream narrative. In the Israeli-Palestinian conflict, we discuss competing narratives, and how new narratives by various academics challenge the official narrative. In the case of Rwanda where the resistance is more clandestine, we demonstrate how the official narrative is challenged by academics and individuals based outside the country. In the case of Sri Lanka, we highlight how two dominant narratives, one by the government and the other by the rebels, competed with the counter-narratives. Overall, we demonstrate how counter-narratives construed to serve as a form of resistance are unfolding in various struggles, and how the gradual impact of academics' agencies on changing hegemonic narratives finds a contextual definition.